Activation of Blood CD3+CD56+CD8+ T Cells during Pregnancy and Multiple Sclerosis - de Andrés, Clara; Fernández-Paredes, Lidia; Tejera-Alhambra, Marta; Alonso, Bárbara; Ramos-Medina, Rocío; Sánchez-Ramón, Silvia (Frontiers in Immunology, 2017)
A striking common feature of most autoimmune diseases is their female predominance, with at least twice as common among women than men in relapsing-remitting multiple sclerosis (RRMS), the prevailing MS clinical form with onset at childbearing age. This fact, together with the protective effect on disease activity during pregnancy, when there are many biological changes including high levels of oestrogens and progesterone, put sex hormones under the spotlight. The role of natural killer (NK) and NKT-cells in MS disease beginning and course is still to be elucidated. The uterine uNKcells are the most predominant immune population in early pregnancy and the number and function of uNK cells infiltrating the endometrium are sex-hormones’ dependent. However, there is controversy on the role of oestrogen or progesterone on circulating NK (CD56dim and CD56bright) and NKT cells subsets. Here we show a significantly increased activation of CD3+CD56+CD8+ cells in MS pregnant women (MSP) compared with non-pregnant MS women (NPMS) (p<0.001) and even with respect to healthy pregnant women (HP, p<0.001), remaining increased even after delivery. The dynamics of expression of early activation marker CD69 on CD3+CD56+CD8+ cells showed a progressive statistically significant increase along the gestation trimesters (T) and at post-partum (PP) with respect to NPMS (1T: p=0.018; 2T: p=0.004; 3T: p<0.001; PP: p=0.001). In addition, early activation expression of CD69 on CD3+CD56+CD8+ cells was higher in MSP than HP in the first two trimesters of gestation (p=0.004 and p=0.015, respectively). NPMS women showed significantly increased cytotoxic/regulatory NK ratio compared with healthy controls (p<0.001). On the other hand, gender studies showed no differences between MS women and men in NK and CD3+CD56+CD8+ cells’ subsets. Our findings may add on the understanding of the regulatory axis in MS during pregnancy. Further studies on specific CD8+ NKT cells function and their role in pregnancy beneficial effects on MS are warranted to move forward more effective MS treatments.